Legal Certainty for Dispute Resolution of the Complete Systematic Land Registration Process (PTSL) through the Village Head in North Buton - Munawir, La Ode; Bariun, La Ode; Kasmira, Wa Ode Nur; Marsalena, Nindy Ade; Suhartiani; Muktiawan, Angga; Surfaena (Dinasti Research, 2025)
This study aims to analyze legal certainty in dispute resolution of the Complete Systematic Land Registration (PTSL) process through Village Heads in North Buton Regency, focusing on the challenges faced in resolving land disputes related to customary rights and territorial boundaries. The PTSL process is expected to provide legal certainty for land rights, but in practice, disputes often arise involving parties claiming land rights, both from a state law perspective. The method used in this study is an empirical juridical approach with case studies in several villages in North Buton Regency. Data collection was carried out through interviews with the Village Head, village officials, the community, and the National Land Agency (BPN), as well as a study of related documents. The results of dispute resolution research are directed to non-litigation resolution with the direct involvement of the dispute head at the North Buton Regency BPN. Referring to the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency, Completion of PTSL activities in the Cluster 2 category, namely land plots whose physical data and juridical data are eligible for the issuance of a Certificate of Land Rights but there are cases in the Court and/or disputes. To ensure legal certainty in the settlement of PTSL disputes through the village head, it needs to be stated in the form of a written agreement by the parties to the agreement that is legally made. Strengthening Coordination between the Village Government, the North Buton National Land Agency. In this study, it was found that the lack of coordination between related institutions led to the slow resolution of land disputes that occurred during the implementation of PTSL.